Tracking dynamically scaled separating objects during a helicopter wind tunnel test - Bruin, A. de; Philipsen, I.; Ryu, M. (My University, 2018)
A wind tunnel test was made to investigate safe dropping of objects from a helicopter, as might be needed during emergency situations. For a correct simulation of the object trajectory, Froude scaling was used, which also required a proper dynamic scaling of the object mass, center of gravity at mass inertia. A rapid prototyping manufacturing technique was used for the dropped objects. On the dropped objects a unique pattern of fluorescent markers was applied and the position of the individual markers was determined by a Stereo Pattern Recognition technique, using two high speed (500 Hz) cameras. Post-processing of these camera images provided detailed information on the object trajectory and the object attitude angles, which were the prime purpose of the tests. With detailed trajectory data available an attempt was made to derive the aerodynamic forces and moments on the object during its fall. This application requires high accuracy of the trajectory data, which could not be reached with the test setup chosen. The paper presents the test setup and model and then focusses on the trajectory measuring system used, the results obtained and a discussion on how the trajectory measurement accuracy might be improved.